A Cytotoxic Test of Ethyl Acetate Extract of Black Sea Cucumber (Holothuria Atra) from Mentawai on HSC-3 Squamous Cell Carcinoma - agung hasnila delfi; Utmi Arma; Dhona Afriza; Okmes Faridyanti; Fauzia Nilam Orienty (FKG Universitas Syiah Kuala, 2026)
Oral squamous cell carcinoma (OSCC) is a malignancy with high global mortality rate. The black sea cucumber (Holothuria atra) is known to contains bioactive compounds such as triterpene glycosides and saponins that exhibit potential anticancer potential. This study evaluated the cytotoxic activity of ethyl acetate extract of Holothuria atra against HSC-3 cells using the MTT assay and determined the IC₅₀ value. An experimental laboratory study was conducted using concentrations of 10, 20, 40, and 80 µg/mL (triplicate). Statistical analysis included univariate analysis, one-way ANOVA, and nonlinear dose-response regression. The results showed significant reduction in cell viability with increasing extract concentrations (p < 0.05). The IC₅₀ value was 41.68 µg/mL, which falls into the category of moderate cytotoxicity according to the National Cancer Institute criteria. The ethyl acetate extract of Holothuria atra demonstrates moderate cytotoxic activity against HSC-3 cells and has potential as an anticancer candidate.